Efektivitas Penggunaan Media Interaktif Berbasis Spinning Wheel untuk Meningkatkan Hasil Belajar Kognitif IPAS Sekolah Dasar - Putri, Setyo Adelia; Lila, Alfi; Ariana, Rani Dwi (Lembaga Yasin AlSys, 2025)
Instruction in Natural and Social Sciences (IPAS) in elementary schools often still relies on conventional methods that are insufficiently engaging and thus fail to optimize students’ cognitive learning outcomes, so there is a need for innovative interactive learning media that can actively and enjoyably involve students. This study aims to analyze the effectiveness of Spinning Wheel–based interactive media in improving cognitive learning outcomes and to examine students’ active engagement in IPAS lessons. The research employed a qualitative method following PRISMA stages, starting from the identification of articles, screening based on relevance, assessment of data and methodological eligibility, and culminating in the inclusion stage to determine the articles suitable for analysis. The results indicate that the use of Spinning Wheel increases learning focus by up to 35%, active participation by 40%, and posttest scores by 25–35% compared with conventional methods. This media also strengthens group discussions, enhances the confidence of lower-achieving students, and creates a more engaging learning atmosphere. Thus, Spinning Wheel constitutes an effective instructional innovation for improving cognitive learning outcomes and active engagement of elementary school students in IPAS learning.